Kelimpahan Makrozoobenthos di Intertidal Muara Sungai Musi Kecamatan Banyuasin II Kabupaten Banyuasin Provinsi Sumatera Selatan - Desi Angraini; Agus Purwoko; Effendi Parlindungan Sagala (Jurnal Penelitian Sains, 2018)
This study aims to calculate the value of the abundance of macrozoobenthos in the Intertidal Musi River Estuary in Sungsang Village, Banyuasin II District, Banyuasin District, South Sumatra Province and to analyze the effect of water salinity on macrozoobenthos in Intertidal Musi River Estuary, Sungsang Village, Ba-nyuasin II District, Banyuasin District, South Sumatra Province. The study was conducted from January 2018 to August 2018, at the Laboratory of Ecology, Department of Biology, Faculty of Mathematics and Natural Sciences, Sriwijaya University, Indralaya. This study includes the test of morishita index and correlation. The results of the study were 4 genera from Bivalvia class, 4 genera from Gastropod class, and 2 families from Poly-chaeta class. The macrozoobenthos abundance in the intertidal Muara Sungsai Musi ranged between 456-854 ind/m2 and the morphic index of each station was included in the grouping and random criteria. Based on the analysis between abundance and salinity, the bottom coefficient (r) is equal to 0.943 which is very strong be-tween salinity and abundance.